Design and Develop Of A Web-Based Purchase Order System At PT. Adhy Mitra Permana - Wijaya, Muhamad Lukman; Bani, Alexius Ulan; Sharyanto, Sharyanto (Journal of Engineering, Technology and Computing (JETCom), 2025)
The design and creation of a web-based Purchase Order System at PT Adhy Mitra Permana, has a background problem, namely the process of ordering the purchase or rental of LED Panels at PT Adhy Mitra Permana is still carried out by recording the order book so that sometimes there are errors in the manual recording process, waste of paper, and the existence of lost data due to recording papers that are sometimes lost so that the system needs to be addressed and payment notes that are written manually and also the process of making reports on income and expenses at PT Adhy Mitra Permana. The system development method used is SDLC and Blackbox testing. System development includes making UML diagrams, namely Use Case, Activity, and Class Diagrams both on the current system and the proposed system. The results obtained from this study are the process carried out with an online web-based information system for LED ordering procedures, report generation, report monitoring and provide convenience in the process to be faster and more structured.